ANALISIS KROMATOGRAFI LAPIS TIPIS (KLT) TERHADAP FRAKSI N- HEKSAN DAN KLOROFORM PADA TANAMAN DAUN BIDARA ARAB (ZIZIPUS MAURITIANA L) - Ulfa, Ana Maria (JIMR : Journal Of International Multidisciplinary Research, 2024)
The Arabian bidara plant (Zizipus mauritiana) is a plant that grows in tropical and sub-tropical areas. The benefits of this plant are anti-inflammatory, analgesic, antipyretic and anticancer (Siregar m, 2020). The aim of this research is to determine the content of chemical compounds found in Arabian bidara plants using thin layer chromatography. This research used samples of the n-Hexane fraction and the chloroform fraction. The method in this research uses chloroform and ethylacetate (7:3) eluents, visual qualitative analysis using thin layer chromatography (TLC). The results of the Retention factor (Rf) values ??produced by samples from the n - Hexane fraction 0,6 the chloroform fraction 0,4 if seen visually using a UV 254 lamp it will glow green and a UV 366 lamp will glow blue. Keywords: Arabic bidara, UV, KLT.